Pygmalion: from Greek Legend to My Fair Lady - Tony T.N. Hung (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
Besides being one of the most popular plays and musicals of all time, Shaw's Pygmalion and its musical offshoot My Fair Lady will always hold a special fascination for teachers and linguists, in particular teachers of phonetics. Is it really possible to transform a common flower girl into a princess merely (or mainly) by changing her pronunciation? And is every successful teacher essentially a kind of Pygmalion figure, creating a new being out of lifeless stone and shaping it in his own way? The present paper traces the development of the Pygmalion legend from its classical origins to its ultimate transformation in Pygmalion (1912) and My Fair Lady (1956), which have in tum spawned plays and musicals in other languages, including Cantonese (Yaotiao Shunu). Various linguistic, sociolinguistic and educational issues thrown up by these modern-day versions - including how pronunciation is taught, the phonological features of different accents, the role of accent in defining a person's social class, linguistic prejudice, and the relationship between teacher and pupil-are touched on.